Perianal fistula and the ileoanal pouch – different aetiologies require distinct evaluation. (14th May 2020) - Reza, L. M.; Lung, P. F. C.; Lightner, A. L.; Hart, A. L.; Clark, S. K.; Tozer, P. J.
Abstract: Aim: Restorative proctocolectomy has been widely adopted as the procedure of choice for restoring gastrointestinal continuity following proctocolectomy. It is often associated with improved quality of life and high patient satisfaction; however, the development of a pouch anal fistula can cause significant morbidity. Pouch fistulas are notoriously difficult to treat and there is great heterogeneity in the management reported of these fistulas. A lack of classification, and the assumption that fistulas originating from completely different aetiologies will behave and respond similarly to a particular treatment strategy, precludes meaningful comparison of management outcomes. We aim to introduce consistency in the reporting of pouch fistulas using a novel classification system. Methods: A consensus process involving clinicians experienced in the management of pouch fistulas from two high volume tertiary centres was performed. Results: We propose that pouch anal fistulas should be classified into four distinct groups according to their aetiology: group 1, anastomotic related; group 2, inflammatory bowel disease related, with sub‐classifications Crohn's (type A) and non‐Crohn's (type B) in origin; group 3, cryptoglandular related; and group 4, malignancy related. Conclusion: Classification of pouch fistulas according to their aetiology will provide consistency in the literature and improve the quality of prospective evidence for the management of pouch fistulas.